Carotid Intima Media Thickness and Its Association With Total Bilirubin Levels in Patients With Coronary Artery Ectasia. (May 2020) - Demirkol, Sait; Balta, Sevket; Celik, Turgay; Unlu, Murat; Arslan, Zekeriya; Cakar, Mustafa; Kucuk, Ugur; Iyisoy, Atila; Barcin, Cem; Demirbas, Seref; Kocak, Necmettin; Cayci, Tuncer
Atherosclerosis plays an important role in the etiopathogenesis of coronary artery ectasia (CAE). The relationship between total bilirubin (TBil) and carotid intima media thickness (cIMT) in patients with CAE has not been fully investigated. Hence, we evaluated the relationship between TBil levels and cIMT in 142 consecutive eligible patients with CAE, newly diagnosed coronary artery disease (CAD), and normal coronary arteries. There were no significant differences in TBil ( P = .772) and cIMT ( P = .791) between the CAE and CAD groups. Bilirubin levels were significantly lower in both CAE and CAD groups compared to the controls ( P < .01). The cIMT was significantly higher in both CAE and CAD groups compared to control participants ( P < .01). A negative correlation between cIMT and TBil was found in all the groups ( P < .01, r = .354). We show for the first time that patients with CAE and CAD have lower TBil and greater cIMT compared to controls with normal coronary angiograms.